Hubungan Kualitas Pelayanan Keperawatan dan Komunikasi Terapeutik dengan Kepuasan Pasien di Rumah Sakit Daerah dr. A. Dadi Tjokrodipo Kota Bandar Lampung - Rachmat Rizkiawan; Linawati Novikasari; Dewi Kusumanignsih (Universitas Malahayati Lampung, 2024)
ABSTRACT The target of patient satisfaction as set by the Health Service Unit of the Ministry of Health of the Republic of Indonesia, target for patient satisfaction at 92%. However, in Bandar Lampung City, specifically at Dr. A. Dadi Tjokrodipo Hospital, patient satisfaction stands at 70%. This indicates a disparity between the Ministry of Health's standards and the current state of hospitals in Bandar Lampung City. This study aims to explore the correlation between nursing service quality, therapeutic communication, and patient satisfaction at Dr. A. Dadi Tjokrodipo Hospital in Bandar Lampung City. This study is a quantitative methodology, employing a cross-sectional design. This study population consist of 124 patients, with a sample size of 96 patients, and selected through purposive sampling techniques. The data collection process by distributing questionnaires. Data analysis included both univariate and bivariate analyses, facilitated by the utilization of the Chi Square test. The majority of respondents within the aged between 35 to 54 years (47.9%). Additionally, the majority of respondents reported a hospital stay duration of two days (40.6%), while a substantial portion held an undergraduate degree (29.2%) and were self-employed (25%). The study revealed a significant correlation between service quality and patient satisfaction, with a p-value of 0.001 (α 0.05), and an odds ratio (OR) of 5.400. Furthermore, a significant correlation between therapeutic communication and patient satisfaction, with a p-value of 0.021 (α 0.05), and an odds ratio (OR) of 2.965. The study's findings suggest the higher service quality and improved therapeutic communication can directly correlate with higher levels of patient satisfaction. Keywords: Nursing Service Quality, Therapeutic Communication, Patient Satisfaction ABSTRAK Target Kepuasan pasien sesuai dalam Unit Pelayanan Kesehatan Kementerian Kesehatan Republik Indonesia yaitu 92%. Namun di Kota Bandar Lampung tepatnya pada RSD dr. A. Dadi Tjokrodipo kepuasan pasien terdapat 70% yang artinya terdapat kesenjangan dari standar yang diberikan oleh kementerian kesehatan dengan salah satu rumah sakit yang ada di Kota Bandar Lampung. Diketahui hubungan kualitas pelayanan keperawatan dan komunikasi terapeutik dengan kepuasan pasien di rumah sakit daerah dr. A. Dadi Tjokrodipo Kota Bandar Lampung. Penelitian ini menggunakan pendekatan kuantitatif dengan desain cross sectional. Populasi penelitian yaitu 124 pasien, dengan dengan jumlah sampel 96 responden, dengan menggunakan teknik purposive sampling. Proses pengumpulan data menggunakan kuesioner. Analisis data meliputi analisis univariat dan bivariat dengan penggunaan uji Chi Square. Sebagian besar responden berusia antara 35 hingga 54 tahun (47,9%). Sebagian besar responden lama masa inap di rumah sakit selama dua hari (40,6%), sebagian besar memiliki pendidikan sarjana (29,2%) dan bekerja sebagai wiraswasta (25%). Adanya hubungan antara kualitas pelayanan dengan kepuasan pasien didapatkan p-value 0,001 (α 0,05), dengan nilai Odd-Ratio (OR) sebesar 5,400. Adanya hubungan antara komunikasi terapeutik dengan kepuasan pasien didapatkan p-value 0,021 (α 0,05), dengan nilai Odd-Ratio (OR) sebesar 2,965. Temuan penelitian ini menunjukkan bahwa kualitas pelayanan yang lebih baik dan komunikasi terapeutik yang lebih baik dapat berkorelasi langsung dengan tingkat kepuasan pasien yang lebih tinggi. Kata Kunci: Kualitas Pelayanan Keperawatan, Komunikasi Terapeutik, Kepuasan Pasien